Synthesis of Iron Oxide Nanoparticles Coated Sand by Biological Method and Chemical Method. (2016) - Rasheed, Raiza; Meera, V.
Abstract: Iron oxide nanoparticles can be prepared by physical, chemical and biological methods. Due to the practical difficulties in using iron oxide nanoparticles for water treatment, these nanoparticles may be coated onto some supports. This paper focuses on the preparation of iron oxide nanoparticles coated sand by biological method using polysaccharide templates and chemical method i.e. sol-gel method. The synthesized particles were characterized using energy dispersive spectroscopy (EDS), scanning electron microscope (SEM) and powder X-ray diffraction analysis (PXRD). From EDS analysis the highest percentage coating of iron on the sand surface was obtained for the iron oxide nanoparticles coated sand synthesized using chitosan templates. The PXRD analysis revealed the crystallite size of the synthesized particles as 42.8 nm. The SEM image showed the presence of almost spherical shaped particles on the sand surface and the coating was discontinuous.